A Reduction in Spikelet Number and Fertility Causes Yield Vulnerability in High‐Yielding Rice. (1st January 2017) - Kobata, Tohru; Ishi, Hibiki; Iwasaki, Hiroyuki
Abstract : Core Ideas: Low irradiance caused by a later end to the rainy season as a result of climate change is of concern in Japan. The objectives of this study were to identify the critical factors causing yield instability in high‐yielding indica‐ and japonica‐dominant rice cultivars released from 1990 to 2010 in Japan over 3 yr with contrasting levels of radiation. In most of these new cultivars, the yield response to the decline in radiant conditions is not well known. The spikelet number decreased with a decrease in solar radiation during the panicle formation stage, such that under low radiation conditions, the benefit of a high spikelet number in the high‐yielding cultivars disappeared. The significant effect of spikelet fertility on grain‐filling under fluctuating radiation levels is specific to the high‐yielding cultivars, whereas in the common cultivars, inadequate grain‐filling in fertilized spikelets is the dominant effect of low irradiance after the middle of the reproductive stage. In Japan, the indica × japonica rice ( Oryza sativa L.) cultivars released since 1990 are high‐yielding under favorable weather conditions. However, climate change may delay the end of the rainy season to midsummer and decrease irradiance in the dominant rice‐growing season. The objectives of this study were to identify the critical yield component factor causing yield instability in these high‐yielding cultivars under fluctuations of solar radiation. One standard‐yield japonica, three high‐yielding japonica‐ dominant, and two indica‐ dominant cultivars were grown in western Japan over 3 yr under contrasting radiation levels. Rough grain yield (RY) ranged from 520 to 980 g m −2 and was positively correlated with spikelet number (SNO). The SNO decreased with a decrease in solar radiation during the panicle‐formation stage; therefore, under low radiation (75% of the highest), the benefit of a high SNO disappeared in the high‐yielding cultivars. A decrease in cumulative radiation during the grain‐filling period decreased both RY and the spikelet‐filling percentage (%F) (RY/potential grain yield [PY]) in the cultivars with high PY. %F was highly correlated with spikelet fertility (%S), where %S was lower in the high‐yielding cultivars than in japonica and fluctuated. There was a higher correlation between %S and cumulative radiation for 2 wk before heading per PY. Restricting the assimilate‐supply by leaf removal near the heading‐time significantly lowered %S. These results suggest that the limitation of the assimilate‐supply due to low irradiance at the panicle‐formation and flowering stages reduces SNO and %S, respectively, which restrains the potential of the high‐yielding cultivars.